Evaluation of the Effectiveness of the Sterilization Process on the Safety of Low-Acid Canned Food Using a Fuzzy Logic System - Nanda Fadilah; Wuliddah Tamsil Barokah; Anisa Raihanah; Mrr Lukie Trianawati; Salmadillah Dwiswara; Muhammad Jundi; Tiara Cahya Iman; Rafa Anargya Putri; Myra Riqqah Widyadhana; Fajrina Aulia Naifa; Rohmi Rihhadatul ‘Aisy; Roma Juliana Arios (Journal of Applied Science, Technology & Humanities | JASTH, 2025)
The sterilization process for low-acid canned foods is a crucial step in ensuring food safety and preventing the growth of harmful microorganisms such as Clostridium botulinum. Inappropriate sterilization temperature or time can affect product and safety. Therefore, a reliable evaluation system is needed. This study aims to assess the effectiveness of the sterilization process for low-acid canned foods using the Mamdani fuzzy logic system. The method used in this study is a systematic literature review of various previous studies on the sterilization process for products such as tuna, pineapple, button mushrooms, gudeg, and canned rendang. Data show that sterilization temperatures range from 110 to 126°C, with processing times between 10 and 50 minutes, resulting in F₀ values ​​between 3.80 and 10.00 depending on the product type. Temperature and time variables are classified into three fuzzy inputs. Food safety outputs are determined based on if-then (F₀ > 3) and unsafe (F₀ < 3) categories. The results of this study indicate that the use of the Mamdani fuzzy logic system can provide a more flexible and accurate evaluation of the sterilization process. This approach can assist in determining appropriate sterilization parameters to ensure the quality and safety of low-acid canned food products